1969
DOI: 10.1002/cber.19691020719
|View full text |Cite
|
Sign up to set email alerts
|

Über die Umsetzung von Phenalen mit vinylogen Formamidinium‐Salzen: Synthese substituierter Pyrene und des Azuleno[5.6.7‐cd]phenalens

Abstract: Die Anionen des Phenalens (1 c) und seiner Derivate 12,13 und 18 setzen sich mit den vinylogen Formamidinium-perchloraten 2 bzw. 7, 8, 10 und 21 zu resonanzstabilisierten, tieffarbigen Enaminen vom Typ 4, Vinylogen des I-Aminomethylen-phenalens, um. Erhitzen der aus l c mit 7a---p, 8 und 10 gebildeten Enamine auf 120-180" fiihrt in hohen Ausbeuten zu gezielt substituierten Pyrenen (6a-p, 9, 11). Analog konnten auch Benzopyrene und aus 22 das pentacyclische Azuleno[5.6.7-cd]phenalen aufgebaut werden.Phenalenonz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1969
1969
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…[74] and was used without further characterization. Compounds 5a, [75,76] 5h, [36] 5i, [37] 13, [54] and 18 [73] are included in the Experimental Section in view of the lack of spectroscopic data in the literature. All other compounds are new (CAS-online January 2000).…”
Section: Methodsmentioning
confidence: 99%
“…[74] and was used without further characterization. Compounds 5a, [75,76] 5h, [36] 5i, [37] 13, [54] and 18 [73] are included in the Experimental Section in view of the lack of spectroscopic data in the literature. All other compounds are new (CAS-online January 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The melting points of compounds were as follows: 9a mp 203-205°C (from ethanol), lit. mp 193-194°C (Jutz et al, 1969); 9b mp 149-151°C (from ethanol), lit. mp 142-144°C (Jutz et al, 1969); 9c mp 134-136°C (from ethanol), lit.…”
Section: Synthesis Of 2-aryl-3-(dimethylamino)allylidene(dimethyl)ammmentioning
confidence: 99%
“…Compounds 9a-c were prepared in relatively high yields from the corresponding phenylacetic acid derivatives, DMF and phosphoryl chloride according to the method described in the literature (Jutz et al, 1969). Compound 9c served as starting material for the preparation of the HPLC internal standard 5c (see below).…”
Section: Synthesis Of 2-aryl-3-(dimethylamino)allylidene(dimethyl)ammmentioning
confidence: 99%
“…A recent investigation indicated that 1,6-naphthyridines possess properties of human cytomegalovirus inhibitors [5]. A number of heterocyclic compounds has been synthesized using Vilsmeier reagent for cyclization purposes [6][7][8][9][10][11][12].In present work the coupling of 4-haloquinolines with 3-aminopyridine by nucleophilic subsitution resulted in quinolinamines. The latter were further cyclized by Vilsmeier-Haak reagent.…”
mentioning
confidence: 89%
“…A recent investigation indicated that 1,6-naphthyridines possess properties of human cytomegalovirus inhibitors [5]. A number of heterocyclic compounds has been synthesized using Vilsmeier reagent for cyclization purposes [6][7][8][9][10][11][12].…”
Section: -Chloro-2-methylquinolines In Reaction With 3-aminopyridinementioning
confidence: 99%